2009
DOI: 10.1007/s00402-009-0955-0
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive osteosynthesis in stable trochanteric fractures: a comparative study between Gotfried percutaneous compression plate and Gamma 3 intramedullary nail

Abstract: PCCP and Gamma 3 have not presented significant differences in any measured parameter for treatment of stable trochanteric fractures. Therefore, the PCCP system is shown to be as minimally invasive as the Gamma 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Failure rates will vary, however, depending on the stability of the fracture type. While most studies included both stable and unstable fracture patterns, Varela-Egocheaga [6] solely focused on stable fracture types noting a failure rate of 3.8%; this can be contrasted with the findings of Sadowski et al [7] who investigated only the most unstable fracture patterns (reverse oblique and transverse intertrochanteric) and noted a significant increase in failure rate to 22.9%. …”
Section: Resultsmentioning
confidence: 99%
“…Failure rates will vary, however, depending on the stability of the fracture type. While most studies included both stable and unstable fracture patterns, Varela-Egocheaga [6] solely focused on stable fracture types noting a failure rate of 3.8%; this can be contrasted with the findings of Sadowski et al [7] who investigated only the most unstable fracture patterns (reverse oblique and transverse intertrochanteric) and noted a significant increase in failure rate to 22.9%. …”
Section: Resultsmentioning
confidence: 99%
“…The literature comparing blood loss in intertrochanteric hip fractures treated with intramedullary nail or DHS is inconclusive. Authors have reported reduced blood loss, [25][26][27] increased blood loss 28 and no difference 29,30 in patients with intertrochanteric fractures treated with an intramedullary nail. The variability among studies may be related to differences in fracture severity, as patients with more displaced fractures are generally more likely to be treated with an intramedullary device.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In stable trochanteric fractures, complication rates of 0%-4% are reported. 3,4 Particularly, varus collapse and cutout of the lag screw pose daunting problems to the surgeon and remain amongst the main causes of treatment failure. 5,6 Inherently unstable fracture patterns in mainly osteoporotic bone in conjunction with the quality of the reduction and screw positioning in the femoral headneck fragment predispose to many complications, including implant cutout.…”
Section: Introductionmentioning
confidence: 99%